Acanthocephalans from Marine Fishes from Patagonia, Argentina - Hernández-Orts, J. S.; Alama-Bermejo, G.; García, N. A.; Crespo, E. A.; Montero, F. E.; Raga, J. A.; Aznar, F.J. (Journal of Parasitology, 2019)
In this study, 542 individual fish from 20 species from the Patagonian continental shelf of Argentina were examined for acanthocephalans. A total of 1,547 acanthocephalans belonging to 5 species were collected from 18 species of fish. Adult forms were represented by 2 species: Aspersentis johni (Baylis, 1929) (Heteracanthocephalidae) from longtail southern cod, Patagonotothen ramsayi (Regan) (new host record), and Breizacanthus aznari Hernández-Orts, Alama-Bermejo, Crespo, García, Raga and Montero, 2012 (Arhythmacanthidae) from raneya, Raneya brasiliensis (Kaup). Immature worms of B. aznari were also collected from the intestine of pink cusk-eel, Genypterus blacodes (Forster) (new host record). Cystacanths of 3 species of Corynosoma Lühe, 1904 (Polymorphidae) were found encapsulated in the mesenteries of fish. Corynosoma australe Johnston, 1937 was the most abundant acanthocephalan in our study, infecting 18 species of fish and accounting for >89.9% of all specimens collected. A cystacanth of Corynosoma bullosum (Linstow, 1892) was found in “castan˜ eta”, Nemadactylus bergi (Norman) (new host record), and cystacanths of Corynosoma cetaceum Johnston and Best, 1942 were collected from red searobin, Prionotus nudigula Ginsburg, and flounders Paralichthys isosceles Jordan (new host record) and Xystreurys rasile (Jordan). The Patagonian shelf of Argentina represents a new locality record for A. johni and C. bullosum. This survey is a starting point for understanding the diversity of marine acanthocephalans in Patagonian waters.